Rancang Bangun Aplikasi E–Learning Berbasis Web pada SMP Negeri 1 Parung - Nirmala, Endar; Jenau, Efrida; Ramdhani, M. Aryo; Saputra, Ripki Adi; Amirulloh, Yuslifar Khalif; Desyani, Teti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
Until now, all the experiences that have developed at SMP NEGRI 1 PARUNG have not changed as they used to do face-to-face systems. This means that schooling and progress among students and teachers must be made depending on the prerequisites that students and teachers meet in class. One strategy that can be done is e-learning. E-learning, helping teachers by distributing materials use the Web without going to class and can be done anywhere. It supports teachers to increase the limited teacher review time. Create e-learning using PHP. PHP is used to create pages and MySQL is used as an information base for information capacity. The results obtained from this e-learning can be applied and implemented to assist educators and students of SMP NEGRI 1 PARUNG in working with the school system.